CAPABILITY CASE STUDY FINE MOTOR SKILLS CHILDREN WITH CEREBRAL PALSY AT CAHAYA KAUTSAR ISLAMIC INCLUSION KINDERGARTEN, EAST JAKARTA - Nanik Rahayu; Rita Aryani; Diana Earlyana Lesmana; Usup; Umi Harti; Saniyya Putri Hendrayana (International Conferences on Early Childhood Education Proceedings, 2023)
This research aims to share information about improving ability and fine motor skills in children who suffer from Cerebral Palsy. The following research has been provided by educators of the Inclusive Islamic Kindergarten Cahaya Kautsar, East Jakarta. This research uses case studies to observe 3 children as subjects who struggle with Cerebral Palsy. The first subject is a girl with the initials ZR the next two are boys with the initials AY and RK, all three children are five years old. Based on the results of this study all three children suffer from different types of cerebral palsy. The stimulation given by the educator to the subjects showed improvement in fine motor skills. Through play activities including squeezing, pinching, arranging different objects, sculpting with playdough, and so on. With this stimulation, teachers can produce development ability fine motor skills that can help children do everyday activities like taking objects, pouring rice, holding pencils, and making crafts.